2007
DOI: 10.1038/sj.ejhg.5201906
|View full text |Cite
|
Sign up to set email alerts
|

New genetic evidence supports isolation and drift in the Ladin communities of the South Tyrolean Alps but not an ancient origin in the Middle East

Abstract: The Alps are one of the most significant geographical barriers in Europe and several isolated Swiss and Italian valleys retain the distinctive Ladin and Romansch languages, alongside the modern majority of Italian and German languages. Linguistically, Ladin belongs to the Romance languages, but some studies on mitochondrial DNA (mtDNA) variation have suggested a major Middle Eastern component to their genealogical origin. Furthermore, an observed high degree of within-population diversity has been interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…Furthermore, the number of haplotypes shared by Ladins from Fassa valleys and those from other alpine areas is relatively low (four with LadB, four with LadG and zero with LadV) and only one haplotype is shared simultaneously among all Ladin groups. This is consistent with the high diversity among Dolomitic Ladin communities reported by Thomas et al 6 On the whole, the data accumulated so far suggest that the genetic heterogeneity among Ladins could be due to the combined effect of a scarce reciprocal genetic exchange, probably due to geographic isolation, and genetic drift.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the number of haplotypes shared by Ladins from Fassa valleys and those from other alpine areas is relatively low (four with LadB, four with LadG and zero with LadV) and only one haplotype is shared simultaneously among all Ladin groups. This is consistent with the high diversity among Dolomitic Ladin communities reported by Thomas et al 6 On the whole, the data accumulated so far suggest that the genetic heterogeneity among Ladins could be due to the combined effect of a scarce reciprocal genetic exchange, probably due to geographic isolation, and genetic drift.…”
Section: Discussionsupporting
confidence: 91%
“…The remaining Trentino populations are scattered in the central group showing a certain degree of genetic heterogeneity (14/28; average Fst, from 0.013 to 0.018). It is interesting to note that the Ladins from the Fassa valley analyzed in this study are genetically separated from the other Ladin groups studied by Thomas et al 6 and Vernesi et al, 40 with all the pairwise genetic distances among these groups of Ladins being statistically significant. Our data set was also compared with a subset of 25 European populations, six of which, in previous studies, had been reported to be isolated (Aromuns from Albany and Macedonia, 41 the Csango from Hungary, 42 the Sardi from Urzulei 43 and the Ladin from the Badia and Gardena valleys in south Tyrol; 6 Supplementary Figure S3 and Supplementary Table S3).…”
Section: Interpopulation Variationmentioning
confidence: 44%
See 2 more Smart Citations
“…We confirmed that Sardinians are genetically differentiated, because of genetic drift and past founder effects, as revealed by the high prevalence of the M26 mutation on the Y chromosome, the low frequency of a derived mutation of the Sardinian-specific Y chromosome haplogroup, as well as the moderate frequency of the UB53a mitochondrial haplogroup. The large number of founder lineages and the high haplotype diversity suggests either a large founding population size, 40 or some degree of genetic admixture. …”
Section: Discussionmentioning
confidence: 99%